Review of soil phosphorus routines in ecosystem models. (April 2020) - Pferdmenges, J.; Breuer, L.; Julich, S.; Kraft, P.
Abstract: We compiled information on 26 numerical models, which consider the terrestrial phosphorus (P) cycle and compared them regarding process description, model structure and applicability to different ecosystems and scales. We address the differences in their hydrological components and between their soil P routines, the implementation of a preferential flow component in soils, as well as whether the model performance has been tested for P transport. The comparison of the models revealed that none offers the flexibility for a realistic representation of P transport through different ecosystems and on diverging scales. Especially the transport of P through macroporous soils (e.g. forests) is deficient. Five models represent macropores accurately, but all of them lack a validated P routine. We therefore present a model blueprint to be able to incorporate a physically realistic representation of macropore flow and particulate P transport in forested systems. Highlights: We review phosphorus models, with a focus on terrestrial process representation. Transport of colloidal P is important in many soils, but neglected in most models. Most models lack processes to simulate preferential flow. A model blueprint is presented to overcome current limitations of P modeling.